Resin push-out bonding strength to root canal dentin: effect of the irrigation solution application prior to post cementation - Michida, Silvia; Dal Piva, Amanda Maria de Oliveira; Tribst, João Paulo Mendes; Souza, Rodrigo Othávio Assunção; Lombardo, Geraldo; Bottino, Marco Antonio; Valandro, Luis Felipe (Brazilian Dental Science, 2017)
Objective: To evaluate the effect of different irrigation solutions prior to post cementation on the resin bonding to bovine root dentine. Material and Methods: 60 bovine roots (16 mm) were prepared to 12 mm with specific drill of a double-tapered fiber post system, included in PMMA, and divided into 6 groups, considering the irrigation solutions (IS) prior to cementation: Gr1- saline solution (control), Gr2- NaOCl 0.5 %, Gr3- NaOCl 1 %, Gr4- NaOCl 2.5 %, Gr5- NaOCl 5 %, Gr6- Chlorexidine 2 % (solution). The root canals were irrigated with IS 20 ml during 10 min. Then they were rinsed with 20 ml of distilled water and dried with paper points. One fiber post was molded with polyvinylsiloxane and 60 posts made of resin cement (PRC) were obtained moments before the cementation. The root canal dentin was etched with H2PO3 37 %/15 s + washing/drying, a multi-bottle etch&rinse adhesive system was applied and the PRC were resin luted with dual resin cement (DuolinkTM, Bisco). Each specimen was cut into 4 slices of ±1.8mm in thickness and submitted to push-out test (1 mm/min). Results: ANOVA showed that bond strength was significantly affected by IS (P